PHARMACEUTICAL AND MEDICAL LAW IN THE FIELD OF HEALTH CARE: ENSURING THE AVAILABILITY OF THE LATEST MEDICAL TECHNOLOGIES AND CIRCULATION OF MEDICINAL PRODUCTS FOR PATIENTS - Haiduchok Ігор; Gumenyuk Ольга; Malekh Надія; Shapovalova Вікторія; Baida Богдана; Shapovalov Валерій; Titarenko Юрій (Actual Problems of Medicine and Pharmacy, 2024)
Established that pharmaceutical and medical law itself regulates the provision of timely, high-quality, safe medical and pharmaceutical care for patients during the circulation of medicinal products of all clinical and pharmacological groups, classification and legal, nomenclature and legal groups in the system of legal relations "doctor-patient-pharmacist” in the field of healthcare and pharmacy. The necessity of implementing EU standards in the sphere of health care of Ukraine has been proved. The functions of medical and pharmaceutical law have been elaborated. The directions and principles of legal consolidation and law-making in the field of health care are outlined. Universal and special principles in the field of health care and pharmacy are summarized. The latest medical technologies are presented to improve medical and pharmaceutical care and improve the quality of life of patients. It has been announced that on November 14-15, 2024, the 21st International Multidisciplinary Scientific and Practical Conference "Medical and Pharmaceutical Law of Ukraine: Organization and Economy of Pharmaceutical and Medical Affairs, Medicines, Technology, Safety, Efficiency, Quality Control, General, Judicial, Evidential and Clinical pharmacy and medicine, pharmacotherapy of health disorders" (Kyiv-Lviv-Tallinn).